Food for the future: ENVIRONMENTAL QUANTIFICATION AND IMPACT REDUCTION - (:unkn) unknown (My University, 2026)
The FOODTURE initiative aims at catalyzing a transformative shift towards sustainable and innovative practices within the European food sector. Through the development and validation of enhanced life cycle assessment (LCA) methodologies and the promotion